PENERAPAN PEMBELAJARAN BERBASIS LINGKUNGAN NYATA UNTUK MENINGKATKAN HASIL BELAJAR PENJASORKES - Nuryanto - Nuryanto (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study was to analyze the implementation of Physical Education learning for grade 8 at MTsN 3 Ponorogo and to find out the development of scientific attitudes and process skills of students in Physical Education learning using the Real Environment-Based method at MTsN 3 Ponorogo. This research is research (field research) with a qualitative research approach. Data collection was carried out using observation, documentation, and interview techniques. Analysis of research data through data reduction, data presentation, and data verification. Then check the validity of the data using data triangulation. The result is that in general, the implementation of Physical Education Class 8 MTsN 3 Ponorogo is going quite well, the implementation of learning using the offline method is carried out in schools by the way the teacher introduces students to plant objects that they want to study then students are asked by the teacher to present their learning results to their friends Yes friend. Whereas in Real Environment-Based learning, the teacher provides material and assignments using WhatsApp grub students are given material and continue to give assignments in the form of swimming videos and practiced at the location of the swimming pool environment and the application of Real Environment-Based learning in Physical Education and Health subjects swimming class 8 MTsN 3 Ponorogo grades knowledge, activeness, cooperation, responsibility among the group has increased.